Verification of the qualitative methods with test devices for detection of drugs of abuse in urine - Jasna Bogdanska; Katerina Tosheska-Trajkovska; Svetlana Cekovska; Sonja Topuzovska; Danica Labudovik (Institute for Public Health of the Republic of North Macedonia, 2018)
The verification of the qualitative method with test devices for detection of eight drugs of abuse in urine (amphetamines, methamphetamine, barbiturates, benzoylecgonine, marijuana, 3,4-methylendioxy-methamphetamine, methadone, and opiates) was done using the assessment results from External Quality Assessment Scheme according to verification protocol in our laboratory, which included predefined performance characteristics such as: accuracy, sensitivity and specificity of the method, as well as for method comparison analysis. Our results have shown that qualitative methods for detection of drugs of abuse in urine have fulfilled the predefined criteria in regard to sensitivity, specificity and accuracy for screening purposes. There was a good agreement between the observed results and assessment results. Reliability of the method has fulfilled the predefined criteria with the exception for amphetamine and methamphetamine (weak and none, respectively). As a conclusion we may say that the rapid non-instrumented test devices for detection of drugs of abuse in urine have shown satisfactory verification results and have fulfilled the criteria for intended purposes according to the ISO 15189 Standard.
Верификација на квалитативни методи со тест ленти за испитување на дроги кои се злоупотребуваат во урина
Keywords: verification; qualitative method; drugs of abuse; urine